2021
DOI: 10.1021/acs.joc.1c00317
|View full text |Cite
|
Sign up to set email alerts
|

Unified Approach to Benzo[d]thiazol-2-yl-Sulfonamides

Abstract: In this paper, we report a unified approach to N-substituted and N,N-disubstituted benzothiazole (BT) sulfonamides. Our approach to BT-sulfonamides starts from simple commercially available building blocks (benzo[d]thiazole-2-thiol and primary and secondary amines) that are connected via (a) a S oxidation/S−N coupling approach, (b) a S−N coupling/S-oxidation sequence, or via (c) a S-oxidation/S−F bond formation/SuFEx approach. The labile N−H bond in N-monoalkylated BT-sulfonamides (pK a (BTSO 2 N(H)Bn) = 3.34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…2C, entry 1). 23 Only traces of product 7a were observed. Detailed investigation and optimization of the reaction steps (sulfenamide formation (entry 2) and its oxidation to sulfonamide (entry 3)) and the isolation and purification of product 7a allowed us to prepare the desired sulfonamide in a reasonable 35% isolated yield (entry 4).…”
Section: Preliminary Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…2C, entry 1). 23 Only traces of product 7a were observed. Detailed investigation and optimization of the reaction steps (sulfenamide formation (entry 2) and its oxidation to sulfonamide (entry 3)) and the isolation and purification of product 7a allowed us to prepare the desired sulfonamide in a reasonable 35% isolated yield (entry 4).…”
Section: Preliminary Resultsmentioning
confidence: 98%
“…Previous observations and data obtained during our research in the field of benzothiazole-2-yl sulfones and sulfonamides showed that sulfone/sylfonamide-bearing C α carbon in the heterocycle is prone to nucleophilic attack. 24–26 We exploited this behaviour, for example, in amine synthesis; 23 however, it also caused the instability of sulfones and sulfonamides on silica gel. 24,27,28 For those reasons we wondered if the quasi-nonexistence of several classes of heteroaryl sulfonamides in the literature 19 might be caused by their instability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations